2019
DOI: 10.1093/icb/icz118
|View full text |Cite
|
Sign up to set email alerts
|

Individual-Level Antibody Dynamics Reveal Potential Drivers of Influenza A Seasonality in Wild Pig Populations

Abstract: Swine are important in the ecology of influenza A virus (IAV) globally. Understanding the ecological role of wild pigs in IAV ecology has been limited because surveillance in wild pigs is often for antibodies (serosurveillance) rather than IAVs, as in humans and domestic swine. As IAV antibodies can persist long after an infection, serosurveillance data are not necessarily indicative of current infection risk. However, antibody responses to IAV infections cause a predictable antibody response, thus time of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Therefore, the large standard deviations observed in the data likely reflect individual biological differences between pigs. These data are consistent with a previous study that demonstrated IAV infection dynamics, lesions and clinical signs were not influenced by the sex of the pig [47].…”
Section: Results For Sex and Treatment Interactionsupporting
confidence: 93%
“…Therefore, the large standard deviations observed in the data likely reflect individual biological differences between pigs. These data are consistent with a previous study that demonstrated IAV infection dynamics, lesions and clinical signs were not influenced by the sex of the pig [47].…”
Section: Results For Sex and Treatment Interactionsupporting
confidence: 93%
“…This knowledge allows estimation of incidence (the number of new infections over time) and force of infection (the rate at which susceptible individuals become infected), quantities that are fundamental to understanding and modeling transmission dynamics (Heisey et al, 2006;Held et al, 2019;Hens et al, 2010) and developing mitigation strategies (Caley and Hone, 2004;Weitz et al, 2020). Knowledge of individual infection times is also relevant to a wide range of pathogen-related factors, including interpretation of the time course of clinical signs of disease (Hawley et al, 2011), vaccine efficacy (Antia et al, 2018), risk factors for infection (Borremans et al, 2011;Pepin et al, 2019), pathogen spillover (Smith et al, 2014), effects of disease on wildlife health and survival (Tersago et al, 2012), host immunity (Epstein et al, 2013) and tracing infection sources (Craft, 2015). However, even though a variety of data sources can theoretically be used to estimate infection time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of individual infection times is also relevant to a wide range of pathogen-related factors, including interpretation of the time course of clinical signs of disease (Hawley et al, 2011), vaccine efficacy (Antia et al, 2018), risk factors for infection (Borremans et al, 2011; Pepin et al, 2019), pathogen spillover (Smith et al, 2014), effects of disease on wildlife health and survival (Tersago et al, 2012), host immunity (Epstein et al, 2013) and tracing infection sources (Craft, 2015). However, even though a variety of data sources can theoretically be used to estimate infection time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wild pigs contact a variety of wildlife species, including bats ( Wang et al, 2018 ), while also contacting humans through hunting ( Bevins et al, 2014 ), living in urban spaces ( Stillfried et al, 2017 ), and intense control programs ( Pepin et al, 2019b ) or with backyard domestic pigs ( Wyckoff et al, 2009 ; Wu et al, 2012 ). As such, pigs have been implicated in the emergence of novel influenza A viruses in humans ( Brown, 2001 ; Hass et al, 2011 ), and human influenza A prevalence is positively correlated with influenza A prevalence in wild pigs ( Pepin et al, 2019a ). Thus, relative to other animal species, pigs may be quite connected to other reservoir species and humans concurrently, while supporting pathogen transmission and evolution with an ample supply of susceptible hosts.…”
Section: Why Might Pigs Contribute To Emergence Of Zoonotic Covs?mentioning
confidence: 99%
“…Applying survival analysis to surveillance data can help remove bias induced by temporally uneven sampling efforts. Survival analysis is widely applicable to commonly-collected disease surveillance data ( Pepin et al, 2019a ; Wilber et al, 2020 ), suggesting that functional epidemiological metrics can be gleaned from opportunistic sampling designs when the sampling design biases are accounted for. A second approach is to apply state-space models that infer epidemiological metrics while accounting for reporting biases ( Chen et al, 2012 ; Miller, 2017 ; Pepin et al, 2017a ; Baker et al, 2019 ; Tabak et al, 2019 ).…”
Section: How Should We Conduct Surveillance?mentioning
confidence: 99%